Hubungan Beban Kerja dengan Stres Kerja Perawat di Rumah Sakit Bhakti Kartini Bekasi - Indah Comala Sari; Siti Rukayah; Diana Barsasella (Jurnal Persada Husada Indonesia, 2017)
Stress is a form of a person's response, both physically and mentally, to a change in his environment that is perceived as disturbing and resulting in threat (flame or flaight). So actually stress is something natural. The purpose of this research is to know the relation of work load with work stress of nurse at Bhakti Kartini Hospital of Bekasi. The place of research is Bakti Kartini Hospital of Bekasi. This research is an analytic research using quantitative approach and using questionnaire. Population in this research is nurse who work in Bhakti Kartini Hospital of Bekasi. Independent variable of work load and dependent variable of work stress. Univariate analysis is used to obtain a picture of the frequency distribution of independent variables (characteristics), (workload) and bivariate used to find the workload relation with nurse work stress. The results obtained from this study is a significant relationship between the length of work (p-value = 0,007), workload (p-value 0,000), with nursing work stress in Bhakti Kartini Hospital Bekasi. From the results of this study can be concluded weight of workload, the higher the work stress, as well as the nurses at Bhakti Kartini Hospital in Bekasi.